Study of Concrete Bearing Behavior for 1067 mm Track Width with Variation in Track Quality Index (TQI) Values - Fistcar, Wawarisa Alnu (Politeknik Perkeretaapian Indonesia Madiun, 2021)
There are many factors that affect the decline in the quality of the railways including the stability of the geometry, the resistance of the upper structure and the lowwer structure of the railways. This research was conducted to determine the effect of geometry instability on the resistance railways structure that is focused on the structure of the railways. In assessing the geometry deviation value of the path using the calculation of the standard deviation each measurement parameter which is then processed into a track quality indexs (TQI). Measurement parameter data is obtained from Galunggung measuring train for 2018 and EM-120 measuring train for 2019. Differences in the calculation of the value of railways quality (TQI) with different years are used as a benchmark for determining the location of a manual survey using a measurement tool and meter listring. The results of field geometry measurements are modeled with a program to help calculate structural strength. Model simulation by analyzing using Finite Element Method (FEM) for several conditions according to the geometry deviation category (TQI). The results of this study found that, concrete sleeper material properties, with concrete compressive (Fc ') 54 MPa and 1400 MPa prestressed wire strength (Fy), rail type is R.54 and ballast property according to PM.60 of 2012. The axial load is working at 16,241 kg, From the analysis of the geometric deviation value of category 3 (25 <TQI <40), it was found that concrete sleeper specimen (B4) experienced compressive stress of 15,566 MPa and tensile stress of 5,178 MPa. Analysis of these conditions, concrete bearings can not rely on the required tensile force that is, 4,632 MPa (0.32 Fc0.67).